Hypoxia-Conditioned Mesenchymal Stem Cells (HC-MSC)-Derived Secretome Gel Induce IL-10 to Improve Diabetic Foot Ulcers via Reduced NF-κB p65 Gene Expression: A Randomized Controlled Trial - Nur Anna Chalimah Sadyah; Heri-Nugroho; Agung Putra; Ignatius Riwanto (International Journal of Biomedicine)
Background: Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus, often leading to severe outcomes. Given the limitations of current treatments, other strategies are needed to address this gap. Recently, the administration of hypoxia-conditioned mesenchymal stem cells (HC-MSC) secretome has shown promise in treating DFUs, particularly in improving wound healing. This study aims to evaluate the efficacy of HC-MSC-derived secretome gel in treating DFUs by assessing its impact on inflammatory biomarkers, specifically IL-10 and NF-κB p65 gene expression. Methods and Results: This randomized, prospective, controlled clinical trial included 16 patients with type 2 diabetes mellitus (T2DM) and Grade 2–3 DFUs. A control group (n=8) was treated with a placebo/base gel, and an intervention group was treated with HC-MSC-derived secretome gel produced by the Stem Cell and Cancer Research Center, Indonesia. The clinical wound volume, IL-10, and NF-κB p65 were assessed pre- and post-treatment. The relative quantification (RQ) of IL-10 showed a significant increase in the intervention group on Day 7 after treatment compared to the placebo group (mean difference of 1.12, P<0.001), indicating an enhanced anti-inflammatory response. The RQ of NF-κB p65 gene expression significantly decreased in the intervention group (mean difference of 0.488, P=0.001), suggesting reduced inflammatory signaling. These results correlate with improved wound healing in the intervention group, evidenced by reductions in wound volume (mean difference of 0.826 cm3, P=0.002) on Day 7 after treatment. Conclusion: HC-MSC-derived secretome gel significantly enhanced IL-10 expression and reduced NF-κB p65 gene expression in DFUs, improving wound healing outcomes. This approach shows promise as an alternative to conventional treatments. Further research is needed to understand the mechanisms involved.